2005
DOI: 10.1016/j.femsec.2004.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Separation of active and inactive fractions from starved culture of Vibrio parahaemolyticus by density dependent cell sorting

Abstract: The co-existence of physiologically different cells in bacterial cultures is a general phenomenon. We have examined the applicability of the density dependent cell sorting (DDCS) method to separate subpopulations from a long-term starvation culture of Vibrio parahaemolyticus. The cells were subjected to Percoll density gradient and separated into 12 fractions of different buoyant densities, followed by measuring the cell numbers, culturability, respiratory activity and leucine incorporation activity. While mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Percoll gradient centrifugation has been used to fractionate E. coli and V. parahaemolyticus cultures during growth phase transition and following starvation, with a variety of results (Makinoshima et al 2002(Makinoshima et al , 2003Nishino et al 2003;Nayak et al 2005). Makinoshima et al (2002Makinoshima et al ( , 2003 indicated that E. coli cultures can be fractionated into more than 20 cell subpopulations and they attributed the cell separation to the increase in buoyant density from exponential to stationary phase of growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Percoll gradient centrifugation has been used to fractionate E. coli and V. parahaemolyticus cultures during growth phase transition and following starvation, with a variety of results (Makinoshima et al 2002(Makinoshima et al , 2003Nishino et al 2003;Nayak et al 2005). Makinoshima et al (2002Makinoshima et al ( , 2003 indicated that E. coli cultures can be fractionated into more than 20 cell subpopulations and they attributed the cell separation to the increase in buoyant density from exponential to stationary phase of growth.…”
Section: Discussionmentioning
confidence: 99%
“…Percoll is regarded as non-toxic to cells (Pertoft 2000;Nayak et al 2005). However, Urografin has been described as toxic to bacterial cells (Kim and Lachman 1982).…”
Section: Discussionmentioning
confidence: 99%